ECONOMIC POLICY IN CONDITIONS OF GEOPOLITICAL SHOCKS – EXPERIENCES OF SERBIA - Jović, Ljiljana; Bošković, Tatjana (ACADEMIC REVIEW, 2025)
This paper presents an overview of economic policy, primarily in the areas of trade and finance, during three major geopolitical crises: the Customs War (1906–1911), United Nations sanctions followed by EU and US sanctions (1992–2000), and the war in Ukraine (2022–present), with reference also to the COVID crisis. The aim of the paper is, by using the comparative-historical method, methods of analysis and synthesis, along with relevant statistical indicators, to identify measures that may be crucial in modeling economic policy under conditions of external shocks. The research results indicate that economic policy, under external geopolitical shocks, is not capable of independently maintaining the economy on a growth trajectory. It is therefore necessary to take into account the broader socio-political context.